Variability among isolates of Alternaria solani causing early blight of potato in eastern Uttar Pradesh - ABHIMANYU; DHARMENDRA KUMAR, AJAY KUMAR*, S.P. PATHAK, JAI P. RAI (Indian Phytopathology, 2016)
Survey of potato fields was carried in six district of three agro-climatic zones (Eastern plain zone, Plane zone and Vindhyan zone) of eastern Uttar Pradesh including main experimental station (MES) of Narendra Deva University of Agriculture and Technology viz., Faizabad, Varanasi (PZ), Kushinagar, Deoria (EPZ), Mirzapur and Sonbhadra (VZ). A. solani isolates from different places of Eastern Uttar Pradesh were found to differ consistently with each other in cultural, physiological and morphological characters. Out of twenty four isolates, Deoria and Mirzapur isolates (D&M) were fast growing ones attaining the colony diameter of 86-90mm while, minimum growth was noted in Kushinagar isolate (K) i.e. 67.50mm after the same period of incubation. The 24 isolates of A. solani collected from different locations were categorized into eight groups viz., As-1 to As-8 based on radial growth, morphological and cultural characters. The maximum conidial size (232-237 x 10-15 ìm) was found in isolate As-8 and minimum (190-195 x 10-15 ìm) in isolate As-1. Maximum growth of A. solani was observed on PDA.